IMPLEMENTASI KEBIJAKAN PROMOSI JABATAN UNTUK PENINGKATAN KINERJA DI PEMERINTAH KABUPATEN SARMI - Herry Kalvin Rumere; Akbar Silo (Universitas Cenderawasih, 2022)
This study aims to identify and analyze the implementation of promotion policies for improving performance within the Sarmi Regency Regional Government and to analyze the inhibiting and supporting factors. This research uses desciptive qualitative approach. The phenomena observed in the research are based on the problems that occur in the Sarmi Regency Regional Government bureaucracy related to the promotion of positions that are not running according to the rules and seem to have elements of nepotism and political policies. Interviews are one of the main methods of collecting data with several informants. Furthermore, the data were analyzed using data reduction, data display, and conclusion drawing. The results of the study indicate that the implementation of promotion policies for improving performance in the Sarmi Regency Regional Government Environment can be seen based on the dimensions of policy implementation in Edward III's theory (communication, resources, disposition, and bureaucratic structure) which shows that the implementation of promotion in the Regency Regional Government Sarmi is quite significant but not optimal because there are still some weaknesses. The inhibiting factors are communication and coordination that are not smooth and effective and some policies are political and do not apply the merit system in the promotion. Supporting factors, namely the quantity of Human Resources is sufficient, as well as the existence of regulations governing promotion and placement of positions.